Literature: Different Perspectives and Approaches in Postcolonial Studies - Karaduman, Alev; Öztürk, Göksel (Peter Lang AG, 2023)
Synergy: Different Perspectives and Approaches in Postcolonial Studies aims at examining and exploring alternative perspectives to postcolonial studies. Accordingly, in the book, the use of postcolonialism in translation studies in literature, the Gothic, the colonial perspective, the issue of immigration, rewriting, and literary criticism are addressed as the subjects of postcolonial studies. © Peter Lang GmbH. Internationaler Verlag der Wissenschaften Berlin 2022. All rights reserved.
Keywords: Bilingualism; Cognitive stylistics; Contrastive rhetoric; Intercultural rhetoric; Morphophonology; Syntactic priming